2019
DOI: 10.1096/fj.201801577rr
|View full text |Cite
|
Sign up to set email alerts
|

Aging‐associated genes and let‐7 microRNAs: a contribution to myogenic program dysregulation in oculopharyngeal muscular dystrophy

Abstract: Oculopharyngeal muscular dystrophy (OPMD) is a late‐onset muscle disease caused by an abnormal (GCN) triplet expansion within the polyadenylate‐binding protein nuclear 1 gene and consequent mRNA processing impairment and myogenic defects. Because a reduced cell proliferation potential and the consequent regeneration failure of aging muscle have been shown to be governed by lethal‐7 (let‐7) microRNA‐mediated mechanisms, in the present study, we evaluated the role of let‐7 in the pathogenesis of OPMD. By a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The Axolotl Lin28/let-7 Circuit 28 (Cappelletti et al, 2019). In turn, the increase of amx-myf-4 transcripts after Lin28 inhibition also supports the notion of an induced muscle differentiation, since the disorganization of muscle fibers was affected, a necessary event for mobilization of satellite cells and interstitial fibroblast cells.…”
Section: Discussionsupporting
confidence: 55%
“…The Axolotl Lin28/let-7 Circuit 28 (Cappelletti et al, 2019). In turn, the increase of amx-myf-4 transcripts after Lin28 inhibition also supports the notion of an induced muscle differentiation, since the disorganization of muscle fibers was affected, a necessary event for mobilization of satellite cells and interstitial fibroblast cells.…”
Section: Discussionsupporting
confidence: 55%
“…Certain miRNAs possess an immunostimulatory motif (UGUGU) and/or serve as TLR7/8 ligands, and some of them are represented in our results: let-7, one of the most highly represented miRNAs in our results for all stimuli; miR-34, also common for all the PAMPs; and miR-133, differentially downregulated after poly I:C challenge. All these miRNAs are related to innate immunity, development, ageing and senescence in molluscs (89), insects (90,91), fish (92), and mammals, including humans (93)(94)(95)(96)(97).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it has been shown that the proliferation capacity of muscle cells, and the regeneration failure in aged muscles, are modulated by let-7 action (Drummond et al, 2011). The increase of amx-pax-7 transcripts after Lin28-1632 treatments could represent a response to a differentiation-inducing stimulus, as occurs in human oculopharyngeal muscular dystrophy, where satellite cells enter to an early proliferative arrest with overexpression of Pax7, MyoG, and Hmgb1, also accompanied by high levels of mature let-7 (Cappelletti et al, 2019). In turn, the increase of amx-myf-4 transcripts after Lin28 inhibition also supports the notion of an induced muscle differentiation, since the disorganization of muscle fibers was affected, a necessary event for mobilization of satellite cells and interstitial fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%